A Qualitative Study Exploring Factors Contributing to Gender Inequality in Rural Ghana - Dako-Gyeke, Mavis; Owusu, Prince (Mediterranean Journal of Social Sciences, 2013)
Gender inequality hinders the development efforts of countries worldwide, especially developing countries. Despite Ghanagovernment’s efforts to address gender inequality, the issue continues to prevail, and invariably retards development mostly inrural communities. This qualitative study, explored factors that perpetuated gender inequality in Kyebi, in the Ashanti Region ofGhana. Purposive and convenience sampling techniques were utilized to recruit twenty-five participants and in-depthinterviews were conducted to gather data for the study. The findings of the study revealed that deep rooted patterns of cultureand socialization continue to perpetuate gender inequality in rural communities denying women equal access to services aswell as to physical and social capital. Based on the findings of our study, we draw attention to the need for research and policyinterventions that would reduce gender inequalities and ensure women’s active participation in social and economicdevelopment.